Iranian nurses’ perceptions of social responsibility: A qualitative study - Faseleh-Jahromi, Mohsen (Nursing ethics, 2014)
Social responsibility is intertwined with nursing; however, perceptions of Iranian nurses about social responsibility has not been explored yet. This study, as part of a larger qualitative grounded theory approach study, aims to explore Iranian nurses’ perception of social responsibility. The study participants included 10 nurses with different job levels. The study data were generated through semi-structured interviews. The participants were selected through purposeful sampling approach, which was then followed by theoretical sampling until reaching the point of data saturation. All the interviews were recorded, transcribed, and analyzed through constant comparative analysis. Positive human characteristics, professional competencies, professional values, solution-focused nursing care, and deployment of professional performance are five categories obtained from the study. The participants believed socially responsible nurses to have positive personality characteristics as well as the necessary skills to do their duties accurately. Such nurses also respect the values, observe the professional principles, and take major steps toward promotion and deployment of the nursing profession in the society.